Dual-polarized IRSs in uplink MIMO-NOMA networks : an interference mitigation approach - Sena, Arthur S. de (2021)
This article has been accepted for publication in a future issue of this journal, but has not been fully edited. Content may change prior to final publication. Citation information: DOI 10.1109/LWC.2021.3099867, IEEE Wireless Communications Letters.